Instrumento de apoio ao planejamento da inovação em combustíveis ecoeficientes para a aviação - Silva, Jéssica Traguetto (2015)
It is anticipated that the next twenty years the air transport will present an increase of almost double the growth rate of world GDP. It is projected that while GDP will grow 3.2%, air and passenger traffic present the average growth 5%. This accelerated expansion of the sector has caused some negative consequences, such as the significant increase in carbon dioxide emissions. The aviation industry has already committed in changing this scenario and the target is to halve CO2 emissions by 2050. To achieve this goal, it is necessary to planning ecoefficient aviation fuel that minimize negative effects such as in the case of substitution of fossil fuels by fuel extracted from renewable resources, which allows the reduction by 80% of CO2 emissions. The identification of alternatives that allow this substitution has been carried out in different research groups, however, it is clear that the planning of innovation has been carried out not integrated manner and also the related literature neglects elements related to innovation management, especially planjeamento . In this sense, this study seeks to fill this theoretical gap and seeks to contribute to this issue by proposing a theoretical method that guides innovation in this sector. From characteristics of tools to support the outstanding innovation of planning in the literature was drawn up the proposed planning method, identified as MEPICE. To check if the method would be considered applicable to the context to which it is addressed, the planning of innovation in eco-efficient fuel, used the Delphi methodology. The result demonstrates the feasibility of MEPICE and suggestions of experts were used in order to improve it.